Can Cephalometrics Discriminate Between the Sexes in a Diverse Juvenile Sample?. Issue 3 (25th November 2016) - O'Donnell, Alexis; Daneshvari Berry, Shamsi; Edgar, Heather J.H.
Abstract: A critical component of the biological profile is sex estimation. Methods commonly used for sex estimation in adults do not work well for juveniles. Population‐specific studies have used cephalometrics to estimate juvenile sex with 80–90% accuracy. Our study attempts to estimate sex in individuals less than 18 years of age using a sample of 1618 lateral cephalograms incorporating all three Angle Class occlusions as well as population diversity. For the sample as a whole, 10 skeletal cephalometrics were found to have significant differences between the sexes. Males and females classify correctly about 50% of the time. Dividing the sample by age groups and race/ethnicity improves results for older age groups and Native Americans, Hispanics, and Asian Americans. Our results indicate that cephalometrics are not useful in determining sex of unidentified juveniles when age and race are not known.